Ok. Here, you can only add like powers. So, we have:
2x^3-5x^3= -3x^3
7x^2-8x^2= -x^2
-3x-6x= -9x
-9-(-9)=0
So the final answer is:
-3x^3-x^2-9x
2007-04-07 08:15:42
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
2x^3 - 3x - 9 + 7x^2 - 5x^3 - 8x^2 - 6x + 9 =
-3x^3 - x^2 - 9x
2007-04-07 08:42:15
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2x^3-3x-9+7x^2 - 5x^3-8x^2-6x+9= -3x^3-x^2-9x
2007-04-07 08:15:20
·
answer #3
·
answered by monu 3
·
0⤊
0⤋
You can only add the terms with the same grade at their variable, so the answer is:
-3x^3 - x^2 - 9x
2007-04-07 08:14:06
·
answer #4
·
answered by IQ DOSON 2
·
1⤊
0⤋
after simplifying we get:
-3x^3 - x^2 -9x
which is
-x(3x^2 +x + 9)
and thats the simpliest form u can get..
unless using complex number in quadratic formula
2007-04-07 08:16:51
·
answer #5
·
answered by xingfumaster 2
·
0⤊
0⤋
-3x^3 - x^2 - 9x
2007-04-07 08:41:05
·
answer #6
·
answered by takxpr 1
·
0⤊
0⤋
-3x^3-x^2-9x
2007-04-07 08:15:04
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
-3x^3-x^2-9x
2007-04-07 08:14:09
·
answer #8
·
answered by humanity_done 3
·
0⤊
0⤋
(2x^3-3x-9+7x^2)-(5x^3+8x^2+6x-9)
2x^3-5x^3=-3x^3
-3x-6x=-9x
-9+9=0
7x^2--8x^2=-x^2
-3x^3-x^2-9x=x(-3x^2-x-9)
2007-04-07 08:28:56
·
answer #9
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
that doesnt make sense
2007-04-07 08:12:43
·
answer #10
·
answered by winonadowney 1
·
0⤊
1⤋